2002
DOI: 10.1161/01.atv.0000030339.79524.6e
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Accelerated Atherosclerosis in Vein Grafts by Placement of External Stent in ApoE*3-Leiden Transgenic Mice

Abstract: Objective-Vein grafts fail because of the development of intimal hyperplasia and accelerated atherosclerosis. Placement of an external stent around vein grafts resulted in an inhibition of intimal hyperplasia in several animal studies. Here, we assess the effects of external stenting on accelerated atherosclerosis in early vein grafts in carotid arteries in hypercholesterolemic apolipoprotein E*3-Leiden transgenic mice. Methods and Results-Venous interposition grafting was performed in apolipoprotein E*3-Leide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…The report by Lardenoye et al showed that relief of this pressure with an external stent placed in vein graft model results in much less VSMC accumulation indicating that mechanical stretch of the vein will stimulate proliferation of venous VSMCs. 19 In cultured VSMCs from veins we have demonstrated that mechanical stretch (15% elongation) significantly stimulates VSMC proliferation as well as the expression of an important growth factor pathway namely, the IGF-1/IGF-1R pathway ( Figures 1, 2, and 3). Interestingly, Hu et al demonstrated that mechanical stretch can directly alter the conformation of the PDGF receptor and initiates signaling pathways that are normally used by PDGF.…”
Section: Discussionmentioning
confidence: 83%
“…The report by Lardenoye et al showed that relief of this pressure with an external stent placed in vein graft model results in much less VSMC accumulation indicating that mechanical stretch of the vein will stimulate proliferation of venous VSMCs. 19 In cultured VSMCs from veins we have demonstrated that mechanical stretch (15% elongation) significantly stimulates VSMC proliferation as well as the expression of an important growth factor pathway namely, the IGF-1/IGF-1R pathway ( Figures 1, 2, and 3). Interestingly, Hu et al demonstrated that mechanical stretch can directly alter the conformation of the PDGF receptor and initiates signaling pathways that are normally used by PDGF.…”
Section: Discussionmentioning
confidence: 83%
“…Apoptosis is associated with decreased plaque stability, and although AnxA5 can affect apoptosis, 13 no differences in apoptotic cell numbers detected with terminal deoxynucleotidyl transferase dUTP nick-end labeling staining were observed at 28 days after surgery. Because apoptosis is known to occur predominantly within 14 days after surgery in this model, 28 effects on apoptosis by AnxA5 on earlier time points cannot be ruled out. Despite there being no change in apoptotic cells numbers after 28 days with AnxA5 treatment, the treatment did reduce vessel plaque instability features, such as endothelial erosion, leaky vessel formation, and severe plaque disruption, in addition to vessel wall thickening, indicating that AnxA5 treatment is effective against both vascular inflammation and the complications of vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The external shielding in the present study might have interfered with mechanical forces, such as shear or tensile stress, which are known to influence intimal hyperplasia [18 -20]. An external support in direct contact to the vessel wall has been shown to reduce intimal thickening in vein grafts [23,24] as well as in balloon-injured arteries [25]. However, the shielding in this study was not in close contact with the vessel wall.…”
Section: Discussionmentioning
confidence: 79%